Drug addiction and families - Barnard, Marina (Jessica Kingsley Publishers, 2007)
"Drawing on a substantial research study comprising interviews with problem drug users and their extended family, Marina Barnard examines the effects of drug use not only on drug users themselves, but also the feelings of anger, sadness, anxiety, shame and loss that are commonly experienced by their extended family. She records the effects of drug use on family dynamics and relationships, including possible social and emotional costs. Its impact on the physical and mental health of family members is also discussed. The author highlights the often overlooked role of grandparents in protecting the children of drug users and considers the perspectives of practitioners such as teachers, social workers and health professionals. The conclusions drawn point to the fact that current service provision, in treating the problem drug user in isolation, fails to address the needs of drug-affected families, and misses the opportunity to develop family-oriented support and treatment." "This accessible book is invaluable reading for drug workers, social workers, health professionals and all practitioners working with families affected by drug use."–BOOK JACKET.